2007
DOI: 10.1111/j.1574-6941.2006.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Roseobacter, Sulfitobacter, Glaciecola and Psychrobacter in seawater collected off Ushuaia, Argentina, Sub-Antarctica

Abstract: Bacterial diversity in sub-Antarctic seawater, collected off Ushuaia, Argentina, was examined using a culture independent approach. The composition of the 16S rRNA gene libraries from seawater and seawater contaminated with the water soluble fraction of crude oil was statistically different (P value 0.001). In both libraries, clones representing the Alphaproteobacteria, Gammaproteobacteria, the Cytophaga-Flavobacterium-Bacteroidetes group and unculturable bacteria were dominant. Clones associated with the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 63 publications
3
61
0
Order By: Relevance
“…Roseobacters have been isolated from seawater, marine sediments, surfaces of marine organisms, and hypersaline ponds (Buchan and Moran, 2005) and can constitute up to 2-8% of surface water bacterioplankton (Wietz et al, 2010;Sunagawa et al, 2015), but the clade can represent as much as 20-40% of sequence data from 16S ribosomal RNA (rRNA) gene libraries especially during algal blooms (Moran et al, 2003;Buchan and Moran, 2005;Prabagaran et al, 2007). Many of the Roseobacter-clade strains are associated with algae and can metabolize dimethylsulfoniopropionate produced by algae (González et al, 2000;Alavi et al, 2001;Miller and Belas, 2004;Buchan and Moran, 2005;Todd et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Roseobacters have been isolated from seawater, marine sediments, surfaces of marine organisms, and hypersaline ponds (Buchan and Moran, 2005) and can constitute up to 2-8% of surface water bacterioplankton (Wietz et al, 2010;Sunagawa et al, 2015), but the clade can represent as much as 20-40% of sequence data from 16S ribosomal RNA (rRNA) gene libraries especially during algal blooms (Moran et al, 2003;Buchan and Moran, 2005;Prabagaran et al, 2007). Many of the Roseobacter-clade strains are associated with algae and can metabolize dimethylsulfoniopropionate produced by algae (González et al, 2000;Alavi et al, 2001;Miller and Belas, 2004;Buchan and Moran, 2005;Todd et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these data suggest that the unique winter clones in clusters J, H and K may represent roseobacters adapted to the winter cold environment in a temperate estuary. Several distinct Roseobacter clusters have been identified in temperate and polar regions based on the 16S rRNA gene marker (Selje et al, 2004;Prabagaran et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Isolation and molecular ecology studies have revealed that the Roseobacter clade occupies diverse marine environments but is most predominant in coastal waters (Buchan et al, 2005). Furthermore, many roseobacters have been found in association with algal blooms (González et al, 2000;Alavi et al, 2001;West et al, 2008), and some roseobacters have been isolated from, and found to be dominant in polar environments (Brown and Bowman, 2001;Brinkmeyer et al, 2003;Selje et al, 2004;Prabagaran et al, 2007). The first complete genome sequence of a marine roseobacter, Silicibacter pomeroyi, was reported by Moran et al (2004), and there are now complete or draft genome sequences for ca.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the cosmopolitan OHCBs discussed above, distribution of the psychrophilic OHCB Oleispira antarctica (55 sequences until now) is thus far limited to the colder waters found at high latitudes [38,39]: the least cold sites at which O. antarctica has been found are Cape Cod (MA, USA, GenBank Acc.Nr.AM117931) 42°04′26″N, 70°12′19″W and South Tasmania [40].…”
Section: Biogeography Of Ohcbmentioning
confidence: 95%